Efeito de diferentes tratamentos de polinização em tomate cereja Solanum lycopersicum var. cerasiforme e berinjela Solanum melongena em casa de vegetação - Silva, Marília Araújo da (2015)
The objective of this study was to evaluate the influence of different types of pollination in the quantity and quality of cherry tomatoes and eggplant grown under greenhouse conditions and the behavior of Scaptotrigona sp. and Melipona subnitida in a greenhouse. The survey was conducted in a greenhouse located on the campus of the Universidade Federal do Semiárido (UFERSA), Mossoró/RN. Two experiments were conducted, and to study with cherry tomatoes we used three colonies of M. subnitida inside the greenhouse and for eggplants we transferred two colonies of Scaptotrigona sp., so one of the colonies was arranged between the rows of plants (colony 1) and the other was placed outside the greenhouse (colony 2) with a tube that allowed free access of forage inside the greenhouse. In the second experiment, the pattern of daily activity of Scaptotrigona sp and the number of bees in and out of the colonies were checked. Temperature measurement was performed in both experiments. To check the pollination requirements in both cultures four treatments were performed: open pollinated, selfpollination, manual pollination by vibration and manual cross-pollination by comparing the quantity and quality of fruit from each treatment, such as weight, length and circumference and number of seeds produced. The results show that the output of bees (Scaptotrigona sp.) of colony 1 starts at 08:00h and ends at 18:00h, though the activity was more intense in the afternoon with elevation at 15:00h. The forage of colony 2 started the activities at 7:00h and ceased at 18:00h, with peak activity at 10:00h, and the activities lasted all day. Both Scaptotrigona sp. as M. subnitida did not visit flowers during the period in which they were kept in the greenhouse. For the tomato crop, the treatment with the highest amount of fruits and the biggest, heavier and with more seeds was Pollination by hand vibration (PVM). For the eggplant, manual cross-pollination treatment (PCM) had the highest values regarding the number of fruit and more seeds when compared to other treatments, however the weight, length and circumference of the fruits did not differ between treatments. However more studies are needed to determine the true potential of Scaptotrigona sp. and M. subnitida as pollinator of crops in the greenhouse